Survival of Colletotrichum dematium in Soil and Infected Mulberry Leaves - Yoshida, S (Plant disease, 1999)
Overwinter survival of Colletotrichum dematium, the causal agent of mulberry anthracnose, was examined in Japan. Conidia and infected mulberry leaves were mixed with soil and placed on the ground in early December. Viability of conidia declined rapidly under field conditions-they could not be recovered within 30 days-whereas conidia placed indoors or outdoors under a roof protected from rain and snow survived longer. When a suspension of soil infested with conidia was used to inoculate detached healthy leaves, no infection was detected after 65 days of incubation, suggesting that conidia in soil are not a significant form of overwintering inoculum. When infected or latently infected leaves incubated in soil under field conditions were used as inoculum on leaves, it was shown that the fungus remained viable for at least 150 days. The fungus in infected leaves maintained under laboratory conditions at different temperatures survived for at least 90 days at 25 and 35°C and for 600 days at 0°C. These results suggest that C. dematium can overwinter in infected or latently infected leaves, and that these leaves can be a source of primary inoculum the following year. Hence, the elimination of fallen leaves in the field in autumn may be an effective way to prevent occurrence of the disease the following year